I don't want to go to bed! - Sykes, Julie (London : Little Tiger Press, 1996)
A little tiger that hates to go to bed scampers away to visit some animal friends.
Keywords: Bedtime-Fiction; Tigers-Fiction; Jungle animals-Fiction